Discovery and Functional Annotation of PRSS1 Promoter Variants in Chronic Pancreatitis. Issue 11 (21st August 2016) - Boulling, Arnaud; Abrantes, Amandine; Masson, Emmanuelle; Cooper, David N.; Robaszkiewicz, Michel; Chen, Jian‐Min; Férec, Claude
Abstract : In the new age of precision medicine, interpretation of the clinical relevance of disease‐associated variants, particularly those rare ones, is most challenging. Herein we illustrate the fundamental importance of functional analysis in this issue, in the context of rare PRSS1 promoter variants. For example, this analysis revealed that c.‐30_‐28delTCC resulted in reduced rather than increased gene expression, suggesting that c.‐30_‐28delTCC is not a predisposing factor for CP as originally postulated. ABSTRACT: Recently, our resequencing of the promoter region of PRSS1 in French Caucasian individuals led to the identification of a functional variant (c.‐204C > A) that is in perfect linkage disequilibrium with the "chronic pancreatitis (CP)‐protective" PRSS1 c.‐408C > T variant. Here, we extended the resequencing to 626 French Caucasians (242 idiopathic CP patients and 384 controls). We discovered three additional variants (c.‐184G > A, c.‐173C > T, and c.‐147C > T), each being found only once in either patients or controls. We analyzed these three variants, together with a known PRSS1 promoter variant (c.‐30_‐28delTCC) long considered to be causative for CP, by luciferase promoter reporter assay in AR42J cells treated with dexamethasone. This analysis revealed that c.‐30_‐28delTCC resulted in reduced rather than increased PRSS1 gene expression, suggesting that it is not a CP risk factor as originally claimed. We provide evidence that c.‐147C > T probably confers protection against CP by reducing the affinity of an ATF4 transcription factor binding site.